A novel quasi-master-slave control frame for PV-storage independent microgrid. (April 2018) - Yang, Jian; Yuan, Wenbin; Sun, Yao; Han, Hua; Hou, Xiaochao; Guerrero, Josep M.
Highlights: A novel quasi-master–slave control frame for PV-storage independent Microgrid is proposed. PVs can simultaneously achieve MPPT and voltage/frequency regulation without communication. A MPPT-based power droop control and an adaptive reactive power control are proposed. The physical and control parameters are designed by the small signal stability of entire system. Effectiveness of the system has been verified by simulation and experimental results. Abstract: In microgrid, photovoltaic (PV) and storage are always combined as a droop-controlled ideal source, which is not very practical. Alternatively, this paper introduces a PV-storage independent system via allocating the PV-storage separately. For this structure, a novel quasi-master-slave control frame is proposed without communication. Storages work as master voltage sources, and PVs operate as current controlled voltage sources (CCVS). For the slave PVs, a MPPT-based power droop control and an adaptive reactive power control are proposed. Thus, PVs can simultaneously achieve maximum energy utilization in real-time and the voltage/frequency regulation. Compared with the conventional master-slave frame, this quasi-master-slave frame is more applicable for allowing a high PV penetration and for unifying islanded and grid-connected modes. Furthermore, the small signal stability of entire system is analyzed to design the physical and control parameters, such as, the minimum capacitance value of DC side, droop coefficients. Finally, simulation and experimental results are presented to verify the system effectiveness.